Numerical prediction of parametric roll in oblique waves. (1st July 2016) - Umeda, Naoya; Sakai, Masahiro; Fujita, Naoki; Morimoto, Ayumi; Terada, Daisuke; Matsuda, Akihiko
Abstract: Numerical prediction of parametric roll in head and following waves has been intensively investigated so that the requirements for a reasonably good prediction are almost entirely known. However, prediction of parametric roll in oblique waves has not yet been sufficiently investigated owing to the unavoidable coupling with sway and yaw motions. Since parametric roll for actual ships occurs with almost zero forward velocity, accurate prediction of the sideways drift of the ship in waves is difficult. Therefore, in this study, the authors present a numerical model of parametric roll in oblique waves by considering low-speed manoeuvring forces. The numerical predictions are compared with newly performed free-running model experiments of a hypothetical ship, in which the maximum roll amplitude was about 20°. The obtained results show that the present model captures some qualitative tendencies in the experiment but the estimated amplitudes are larger than the experiment by about 7°. This information can be used to identify the minimum requirements for good prediction of parametric roll in oblique waves. Highlights: We develop a 5 DOF numerical model for parametric roll in oblique waves. The numerical results were compared with model experiments. Reasonable agreement was presented and reasons of discrepancy were discussed.